2016
DOI: 10.1101/071159
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensory neuron fate is developmentally perturbed byGarsmutations causing human neuropathy

Abstract: Charcot-Marie-Tooth disease type 2D (CMT2D) is a peripheral nerve disorder caused by dominant, toxic, gain-of-function mutations in the widely expressed, housekeeping gene, GARS. The mechanisms underlying selective nerve pathology in CMT2D remain unresolved, as does the cause of the mild-to-moderate sensory involvement that distinguishes CMT2D from the allelic disorder distal spinal muscular atrophy type V. To elucidate the mechanism responsible for the underlying afferent nerve pathology, we examined the sens… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Additional analyses of other tRNA synthetase disease-causing mutants in Drosophila or in mouse models lead to similar conclusions that the disease is not due to a loss of the canonical function of these enzymes (Ermanoska et al, 2014;Storkebaum et al, 2009;Stum et al, 2011). On the contrary, recent studies have shown that tRNA synthetase mutations strikingly lead to toxic gains of function, impairing the signaling of different neurotrophic factor receptor families in the nervous system (He et al, 2015;Sleigh et al, 2017aSleigh et al, , 2017bStum et al, 2011). Thus, a class of diseases thought to be caused by impaired local translation in compartmentalized signaling is actually caused by the perturbation of another compartmentalized signaling mechanism orchestrated by neurotrophic factors.…”
Section: Pathological Consequences Of Deficits In Compartmentalized Signalingmentioning
confidence: 89%
“…Additional analyses of other tRNA synthetase disease-causing mutants in Drosophila or in mouse models lead to similar conclusions that the disease is not due to a loss of the canonical function of these enzymes (Ermanoska et al, 2014;Storkebaum et al, 2009;Stum et al, 2011). On the contrary, recent studies have shown that tRNA synthetase mutations strikingly lead to toxic gains of function, impairing the signaling of different neurotrophic factor receptor families in the nervous system (He et al, 2015;Sleigh et al, 2017aSleigh et al, , 2017bStum et al, 2011). Thus, a class of diseases thought to be caused by impaired local translation in compartmentalized signaling is actually caused by the perturbation of another compartmentalized signaling mechanism orchestrated by neurotrophic factors.…”
Section: Pathological Consequences Of Deficits In Compartmentalized Signalingmentioning
confidence: 89%